The Study Of Cement Properties With Ceramic Waste Fillers - Sharil Azuar, Wan Nur Syahidah (Universiti Sains Malaysia, 2022)
Due to a continuously expanding global population and the desire to satisfy consumer demands, landfills will continue to receive vast quantities of waste. Changing a substantial quantity of solid waste into an alternative resource can assist conserve diminishing non-renewable material supplies, sustain essential energy, and alleviate environmental and landfill issues. Ceramic waste (CW) has the potential to be employed as an effective supplementary cementitious material (SCM) in cement-based materials due to its high silica-alumina content. Utilizing CW as an alternative concrete ingredient will positively affect the environment. However, there is still a paucity of knowledge about using CW as a raw material in the production of eco-friendly cement. The aim of the research is to characterize the ceramic sample to determine its suitability as partial replacement in Ordinary Portland Cement (OPC) and to figure out the best conditions for synthesizing an eco-friendly cement using CW. The OPC and CW will be characterised using Scanning Electron Microscopy (SEM), X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Particle Size Analysis (PSA) investigations preliminary to sample preparation. The eco-friendly cement is then sintered at various temperatures after being produced to a specific mineralogical composition. The gypsum addition will be added to cement mixtures to delay hydration. Analytical procedures such as XRF, SEM, and PSA will be used to characterise the final sample. Because the primary compounds were fully reacted and hydraulic active chemicals predominated in the products, 1100°C was revealed to be the ideal sintering temperature for eco-friendly cement. These findings were backed up by XRD, XRF, and SEM analysis. As a result, study reveals that ceramic waste can be used as raw materials to make ecologically friendly cements.